Semantics of Symbolic Decoration on Macedonian Traditional Movable Furniture from 19th Century - Nikoljski panevski, Elena (Faculty of Forestry, University of Zagreb, 2016)
The analysis of symbolic decoration on movable furniture is a process defined by expressing the inner world of thoughts and ideas through to the outside, living world. The furniture and other household equipments ware made with high functionality. Functionality of the furniture was most important, more precisely it's aestetics was a result of the functionality. The world of the symbolic decoration was a personal, intimate or for the family, but despite that it does came from thoughts and the hands of self-taught carpenter / the host, analyzes reveal deep cosmological links and images with the past and the tradition and their repetition in history. Therefore the aim of the paper is to analyze the process of creating the decoration and semantics of the Macedonian traditional movable furniture from the 19th century. Researches and analysis was made in the Republic of Macedonia, more specifically in the several villages around the mountain Skopska Crna Gora and from the Tetovo region village Dzepciste, and the region of the citty of Veles. Based on measurements of the object, photos, drawings, foto-documentation, the paper exposed their real and actual appearance. Based on these drawings there are analyses made of symbols and forms, and a deeper analysis of the religious context under tainable impact incurred. The analyzes showed that the symbolic decoration of movable furniture in the Macedonian traditional house from the 19th century has its roots in the past that as the archetypal signs follow the furniture through the ages. The purpose of the paper is this analysis of cosmological pictures of the furniture to be clearly described and perhaps in the future transposed in a new modern context.
Keywords: semantic; symbolic decoration; Antique context; Christian context; identification; formalization; cosmological character of decoration; expression; traditional furniture